Measuring and Explaining the Impact of Productive Efficiency on Economic Development - Jayasuriya, Ruwan; Wodon, Quentin (Published by Oxford University Press on behalf of the World Bank, 2014)
A limitation of most empirical cross-country studies that focus on determinants of gross domestic product (GDP) is that they fail to distinguish explicitly between inputs used in production and conditions that facilitate production. For example, physical capital, human capital, and labor are production inputs, whereas the quality of institutions, macroeconomic stability, and market quality are conditions that facilitate production. This article takes this distinction seriously and uses a stochastic frontier approach to study factors affecting economic performance. A panel data set of 71 countries for the 1980-98 periods is used to estimate a production frontier with physical capital, human capital, and labor as inputs. The article also analyzes what drives productive efficiency, using the institutional framework, macroeconomic stability, market quality, and urbanization as possible explanatory factors. Urbanization turns out to be an important determinant, with the rule of law, inflation rate, and market quality also affecting productive efficiency.